ENHANCING FUTURE ENGINEERS’ PROFESSIONAL SKILLS THROUGH THE FLIPPED CLASSROOM METHOD (International Educators Conference, 2025)
The rapidly evolving field of engineering demands that future professionals possess not only technical knowledge but also critical thinking, communication, and teamwork skills. The flipped classroom method offers a transformative approach to engineering education by shifting passive content delivery outside of class and dedicating in-class time to active, collaborative learning. This method encourages students to engage deeply with material, apply theoretical concepts through problem-solving and discussions, and receive immediate feedback from instructors and peers. By fostering self-directed learning and enhancing interactive engagement, the flipped classroom effectively develops the professional competencies essential for modern engineers. This article explores how integrating the flipped classroom method into engineering curricula can better prepare graduates for the complexities of their future careers.